Compliance of Philippine jeepneys with selected national vehicle regulations and standards - Dela Cruz, Raphael Christian C.; Marabut, Abighael Dawn Z.; Vergel, Karl B. N. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
The main purpose of this study is to assess the compliance ofjeepney models with the existing regulations and standards of the Land Transportation Office Motor Vehicle Inspection System. Vehicle specification data are obtained from DOST-PCIEERD (Department of Science and Technology - Philippine Council for Industry, Energy and Emerging Technologies Research and Development) that conducted the survey of jeepney models in the different regions of the Philippines. The survey consisted of specifications which were cross checked with the actual vehicle. Compliance rate for each specification is assessed. With this, it has been analyzed that basic dimensional standards from Land Transportation Office Motor Vehicle Inspection System (LTOMVlS) are complied by all models, while safety standards like seatbelts and windshield glass have low compliance rates. Recommendations for the supplementary improvement of the regulations regarding vehicle dimensions derived from anthropometric measurements are proposed to improve comfort and convenience to passengers of future jeepney models.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Commercial vehicles -- Standards -- Law and legislation -- Philippines